ps3a - Problem Set#3Answer Key 1 Basics Consider the...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Problem Set #3Answer Key 1 Basics Consider the utility function u = x α y 1- α . Answer: For this utility function, find: 1. Demand functions. Set up the Lagrangian: L = x α y 1- α + λ ( I- p x x- p y y ) This gives the first order conditions: αx α- 1 y 1- α- λp x = 0 (1- α ) x α y- α- λp y = 0 I- p x x- p y y = 0 The first two equations together imply that αy (1- α ) x = p x p y , which also means that y = (1- α ) p x αp y x . Plugging this into the last equation and solving gives the answers: x * = αI p x , y * = (1- α ) I p y 2. Compensated Demand functions. Answer: for this case, we set up the lagrangian “backwards:” L = p x x + p y y + λ ( u- x α y 1- α ) This gives the first order conditions: ∂L ∂x = p x- λαx α- 1 y 1- α = 0 ∂L ∂y = p y- λ (1- α ) x α y- α = 0 ∂L ∂λ = u- x α y 1- α = 0 1 The first two equations together once again imply that αy (1- α ) x = p x p y- they are identical to those from the previous problem!. Thus, we once again have y = (1- α ) p x αp y x . Plugging this into the last equation gives: u = x α parenleftbigg (1- α ) p x αp y x parenrightbigg 1- α Simplifying gives: x c = u parenleftbigg αp y (1- α ) p x parenrightbigg 1- α Repeating the same steps for y gives: y c = u parenleftbigg (1- α ) p x αp y parenrightbigg α 3. The Expenditure function. Answer: to find the expenditure function, we simply use our compensated demand functions from the previous problem in the expression: E = p x x c + p y y c Plugging in gives: E = p x u parenleftbigg αp y (1- α ) p x parenrightbigg 1- α + p y u parenleftbigg (1- α ) p x αp y parenrightbigg α This can be simplified to read: E = up α x p 1- α y bracketleftBigg parenleftbigg α 1- α parenrightbigg 1- α + parenleftbigg 1- α α parenrightbigg α bracketrightBigg 4. The Indirect Utility function. Answer: Here, we plug the regular demand functions back into the utility function, with result: V...
View Full Document

This note was uploaded on 11/12/2009 for the course ECONOMICS 701 taught by Professor Baker during the Spring '09 term at CUNY Hunter.

Page1 / 6

ps3a - Problem Set#3Answer Key 1 Basics Consider the...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online